Pulse Therapy in Rituximab Era: A Retrospective Study of 124 Patients of Pemphigus from a Tertiary Care Center of South Rajasthan - Asit Mittal; Rini Makhija; Manju Meena; Manisha Balai; Lalit Kumar Gupta; Sharad Mehta (Wolters Kluwer Medknow Publications, 2024)
Background: Pemphigus is a potentially life-threatening autoimmune blistering disease which characteristically affects skin and mucosae. Pulse therapy for the treatment of pemphigus has been in vogue for several years and considered better than conventional corticosteroids. Aims and objectives: This study was conducted to evaluate the efficacy and safety of pulse therapy in pemphigus patients treated over a period of 10 years. Materials and Methods: This retrospective study was based on medical records of Pemphigus patients treated at Department of Dermatology from January 2008 to December 2017. Diagnosis of pemphigus was made on clinical ground, Tzanck smear and histopathology of skin/mucous membrane lesions. Patients were put on DCP/DAP depending on the completion of family. Results: A total of 124 patients were included in the study. Age of patients ranged from 18 years to 72 years with mean of 41.21±12.71 years. Amongst 124 patients, 114 (92%) had pemphigus vulgaris and 10 (8%) had pemphigus foliaceous. 89 patients received DCP and 35 patients received DAP therapy. Number of pulses received by patients in phase I ranged from 4 to 27, average being 8.16±4.63. 106 patients completed the phase I of which 83 completed the phase II. 54 patients had successfully completed phase III of which 22 are currently in phase IV and 28 patients have completed their five year follow up period and considered as cured. Conclusion: Pulse therapy is a cheap and easily available mode of therapy in treatment of pemphigus in India even in the present era of modern molecules like Rituximab. With pulse therapy, it is now possible to induce and maintain remission, and achieve cure, provided the patients strictly adhere to the prescribed schedule.